2021
DOI: 10.18632/aging.203796
|View full text |Cite
|
Sign up to set email alerts
|

rTMS alleviates AD-induced cognitive impairment by inhibitng apoptosis in SAMP8 mouse

Abstract: This study sought to investigate whether repetitive transcranial magnetic stimulation (rTMS) could alleviate cognitive dysfunction in SAMP8 mice by reducing cell apoptosis and activating the cAMP/PKA/CREB signalling pathway. A total of 40 SAMP8 mice were randomly assigned to the SAMP8 group (n=20), and rTMS treatment group (rTMS+SAMP8, n=20); additionally, 20 homologous and normal aged SAMR1 mice were used as the control group(n=20). The Morris water maze and Y maze tests were applied to evaluate spatial learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The similar performance was observed in our study and just showed a positive change in response to rTMS treatment. Animal studies on mice reported that rTMS were able to ameliorate cognitive deficits due to AD and improve memory ability by changing the electrophysiological properties of the hippocampus and increasing neuronal excitability 28 . rTMS may be a promising useful tool as single or combined therapy for individuals with memory decline due to MCI and AD.…”
Section: Discussionmentioning
confidence: 99%
“…The similar performance was observed in our study and just showed a positive change in response to rTMS treatment. Animal studies on mice reported that rTMS were able to ameliorate cognitive deficits due to AD and improve memory ability by changing the electrophysiological properties of the hippocampus and increasing neuronal excitability 28 . rTMS may be a promising useful tool as single or combined therapy for individuals with memory decline due to MCI and AD.…”
Section: Discussionmentioning
confidence: 99%
“…112,113 Accumulating studies show that rTMS could modulate neural apoptosis in the brain of patients with AD. 85,107,114 We previously found that a 1-month iTBS treatment reduces caspase-3 and Bax levels and increases the expression of Bcl-2, and therefore, suppresses the number of TUNEL-positive cells in the hippocampus of APP/PS1 mice, suggesting the antiapoptotic effects of rTMS in AD. 85,102 Consistent with our findings, previous studies also indicated that rTMS inhibited neuronal apoptosis in other animal models such as 3xTg-AD mice 107 and trimethyltin (TMT)-induced Alzheimer's-like rat models, 115 in which the rTMS-induced antiapoptotic effects, that were related to the modulation of PI3K/Akt/ GLT-1 or PI3K/Akt/mTOR signaling pathways.…”
Section: The Cellular Mechanism Of Rtms Treatment In Admentioning
confidence: 97%
“…These neurotransmitters are pivotal in excitatory and inhibitory synaptic transmission, influencing cellular responses and network activity. cAMP and PKA signaling: TMS-induced neuronal depolarization can activate cyclic adenosine monophosphate (cAMP) and protein kinase A (PKA) signaling pathways [ 77 ]. These pathways are involved in intracellular signal transduction and modulation of gene expression.…”
Section: Basic Theory Of Transcranial Magnetic Stimulationmentioning
confidence: 99%